Part 2: Nurses' career aspirations to management roles: qualitative findings from a national study of Canadian nurses. (25th October 2012) - Wong, Carol A.; Spence Laschinger, Heather K.; Macdonald‐Rencz, Sandra; Burkoski, Vanessa; Cummings, Greta; D'amour, Danielle; Grinspun, Doris; Gurnham, Mary‐Ellen; Huckstep, Sherri; Leiter, Michael; Perkin, Karen; Macphee, Maura; et al.
<x xml:space="preserve">Abstract</x> Aim Our aim was to investigate direct‐care nurses' interests in formal management roles and factors that facilitate their decision‐making. Background Based on a projected shortage of nurses by 2022, the profession could be short of 4200 nurse managers in Canada within the next decade. However, no data are currently available that identify nurses' interests in assuming manager roles. Methods Using focus group methodology, we conducted 18 focus groups with 125 staff nurses and managers in four regions across Canada. Results Major themes and subthemes influencing nurses' decisions to pursue management roles included personal demographic (education, age, clinical experience and life circumstances), personal disposition (leadership skills, intrinsic rewards and professional commitment) and situation (leadership development opportunities, manager role perceptions and presence of mentors). Although nurses see management roles as positive opportunities, they did not perceive the rewards to be great enough to outweigh their concerns. Conclusions Findings suggested that organizations need to provide support, leadership development and succession opportunities and to redesign manager roles for optimum success. Implications for nursing management Leaders need to ensure that they convey positive images of manager roles and actively identify and support staff nurses with leadership potential.